1990
DOI: 10.1093/ajcn/51.4.558
|View full text |Cite
|
Sign up to set email alerts
|

Energy supplementation and the nutritional status of hemodialysis patients

Abstract: Twenty-one patients undergoing regular hemodialysis completed a trial of energy supplementation. Nine patients added the glucose polymer Polycose to their usual diet and 12 acted as control subjects. The supplemented patients were asked to incorporate 100 or 150 g polymer, equivalent to 1600 or 2400 kJ (400 or 600 kcal) into their usual diet, daily for 6 mo. This resulted in a mean increase in energy intake of 1630 kJ (p less than 0.05) and a mean weight gain of 3.1 kg (p less than 0.005). The addition of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 8 publications
1
61
0
1
Order By: Relevance
“…Parenteral intradialytic calorie and amino acid supplementation has been shown to acutely reverse the net negative whole body-forearm muscle protein balance [10], increasing body weight, serum albumin and ApoA-I levels without altering plasma lipid concentration in ESRD patients maintained on hemodialysis. Moreover, trial of energy supplementation via addition of the glucose polymer Polycose to the usual diet for 6 months has been shown to significantly increase total and lean body mass, with no significant effect on plasma triglyceride level [11], in hemodialysis patients. Observational studies have shown that in patients with CKD Stages 3-5, the rate of decline in glomerular filtration rate is higher in patients with low energy intake than in patients with moderate or high energy intake [12].…”
Section: Introductionmentioning
confidence: 99%
“…Parenteral intradialytic calorie and amino acid supplementation has been shown to acutely reverse the net negative whole body-forearm muscle protein balance [10], increasing body weight, serum albumin and ApoA-I levels without altering plasma lipid concentration in ESRD patients maintained on hemodialysis. Moreover, trial of energy supplementation via addition of the glucose polymer Polycose to the usual diet for 6 months has been shown to significantly increase total and lean body mass, with no significant effect on plasma triglyceride level [11], in hemodialysis patients. Observational studies have shown that in patients with CKD Stages 3-5, the rate of decline in glomerular filtration rate is higher in patients with low energy intake than in patients with moderate or high energy intake [12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Allman el al. [10], after ran domly allocating oral energy supplements during 6 months, reported an improvement in body composition of 9 MHD patients. This supplement was composed of about 450 kcal/ day glucose polymer.…”
Section: Enteral Supportmentioning
confidence: 90%
“…These diets, if not carefully monitored, may be hypocaloric [8,9] and may impair the patient's nutritional status before starting the dialysis treatment. After starting dialysis, pa tients usually report spontaneous low energy intake [10], This has recently been observed in the pilot Mortality and Morbidity in Main tenance Hemodialysis Study [11] in patients entering the study (28 keal/kg body weight/ day without diabetes and 25 keal/kg/body weight/day with diabetes). Such low energy intakes might explain why these chronically diseased patients are frequently malnour ished.…”
Section: Causes Of M Alnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces données, observées indépendamment de l'état inflammatoire évalué par la C-réactive proteine sérique, démontrent l'inté-rêt du suivi diététique dans cette population. Plusieurs études contrôlées ont mis en évidence une amélioration de l'état nutritionnel lors de la supplémentation orale [30][31][32][33][34][35]. Une amélioration de la prise alimentaire spontanée lors de la prise de suppléments oraux a également été rapportée [35,36].…”
Section: Prise En Charge De La Dénutrition -Nutrition Parentérale Perunclassified